2017
DOI: 10.1051/matecconf/201710102011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pretreatment using sodium hydroxide and acetic acid to biogas production from rice straw waste

Abstract: Abstract. Rice straw is agricultural waste containing high potency to be treated to biogas. However, the usage of rice straw is still limited due to high lignin content that will cause low biodegradability. The aim of this research was to study the effect of pretreatment using NaOH and acetic acid to biogas production from rice straw. NaOH was varied from 2%w, 4%w, and 6%w; and acetic acid was varied from 0,075 M, 0,15 M dan 0,75 M. The rice straw was cut into 1 cm size and submerged for 30 minutes in NaOH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The main compositions of biogas are CH 4 (60-70%) and CO 2 (28-38%) and various gas products such as H 2 S and N 2 . Biogas production raw materials generally come from agricultural waste such as rice husks [31], rice straw [8,33], wheat straw [15] and livestock waste such as cow dung [24], sugar cane [32], Eichhornia crassipes [35], horse manure, pig manure and poultry manure [14]. There are also biogas raw materials derived from industrial waste alcohol [9][10][11][12], slaughterhouse wastes [6], fish industry waste [28], cassava starch [5], and tapioca industrial liquid waste [2,20].…”
Section: Introductionmentioning
confidence: 99%
“…The main compositions of biogas are CH 4 (60-70%) and CO 2 (28-38%) and various gas products such as H 2 S and N 2 . Biogas production raw materials generally come from agricultural waste such as rice husks [31], rice straw [8,33], wheat straw [15] and livestock waste such as cow dung [24], sugar cane [32], Eichhornia crassipes [35], horse manure, pig manure and poultry manure [14]. There are also biogas raw materials derived from industrial waste alcohol [9][10][11][12], slaughterhouse wastes [6], fish industry waste [28], cassava starch [5], and tapioca industrial liquid waste [2,20].…”
Section: Introductionmentioning
confidence: 99%
“…Further on simulators saccharification and fermentation it produced 86.7% ethanol produce. Few renewals are available on pretreatment of eucalyptus with alkaline medium, suggesting that it is a less expensive technique. Through the process inventories, it is observed that the hot water treatment is energy consuming.…”
Section: Organic Solventsmentioning
confidence: 99%
“…Based on previous work, one of the best ways to produce biogas is using the anaerobic digestion method [4]. Anaerobic digestion is commonly used as a method to treat organic waste [5][6]. While anaerobic digestion can reduce pollution, it can also provide an energy source in the form of biogas.…”
Section: ■ Introductionmentioning
confidence: 99%